Francie jako aktér v Arktidě - Domkář, Michal (Univerzita Karlova, Fakulta sociálních věd, 2023)
This bachelor's thesis deals with the modern French Arctic policy and its gradual evolution. A crucial prerequisite is the transformation of the Arctic narrative, that is how the region is generally seen. While it had been previously understood as a place for international cooperation, global warming has dramatically changed the region. Thus, both the key points of the Arctic debate and its participants and the overall narrative have changed. The goal of this thesis is to find out whether France reflects this change of the narrative and if so, how. France has shown interest in the region for a long time and its long-lasting presence makes it an important actor. The research has been done through the analysis of relevant government documents and proclamations which demonstrate the official country's approach the best. The resulting findings confirmed the transformation of Arctic policy, which changes its main proclaimed interest over time. The emphasis is no longer on scientific activity as it once was. Although it is increasingly incorporating security and the strategic importance of the region into its approach, given the recency of the phenomenon, it cannot yet be said with certainty that this will become the central focus of future policy, although the trend described suggests that it will. Tato práce se zabývá současnou francouzskou arktickou politikou a jejím postupným vývojem. Stěžejním předpokladem práce je proces proměny arktického narativu, tedy způsobu obecného nahlížení na region. Zatímco dříve byla oblast vnímána jako prostor pro mezinárodní spolupráci, globální oteplování dramaticky změnilo povahu regionu. Změnily se tedy jak klíčové body arktické debaty a její účastnící, tak celkový narativ. Cílem této práce je zjistit, zda Francie reflektuje tuto proměnu arktického narativu a upravuje dle ní svoji vlastní politiku a pokud ano, jak. Francie o region jeví zájem již dlouho a její dlouholetá přítomnost v regionu z ní činí velmi důležitého aktéra. Výzkum byl proveden analýzou relevantních vládních ...